3d transition metal embedded C2N monolayers as promising single-atom catalysts: A first-principles study. (August 2016) - Ma, D.W.; Wang, Qinggao; Yan, Xunwang; Zhang, Xiwei; He, Chaozheng; Zhou, Dawei; Tang, Yanan; Lu, Zhansheng; Yang, Zongxian
Abstract: Using first-principles calculation, the potential of the very recently synthesized graphene-like C2 N monolayers as the single-atom catalyst (SAC) substrates for the 3 d transition metal (TM) (Sc to Zn) has been studied. The calculated energies indicate that the early 3 d TM (i.e. Sc, Ti, V, Cr, and Mn) embedded C2 N monolayers are the very promising SACs, because these TM single atoms can be strongly trapped in the cavity of the C2 N monolayer and exist in the isolated form. The CO oxidation as a probe reaction was investigated to examine the catalytic activity of the predicted SACs. The strong adsorption and significant activation of the reactants CO and O2 molecules were observed. Due to the much stronger binding of O2 than CO, the CO oxidation on these SACs should proceed via a two-step Eley–Rideal reactions. The results reveal that the highest energy barriers for the CO oxidation on the Cr and Mn embedded C2 N monolayers are merely 0.59 and 0.64 eV, respectively. Therefore, Cr and Mn embedded C2 N monolayers are the very promising SACs for the low-temperature CO oxidation reaction. The study presented here suggests that the C2 N monolayers are the promising platforms to synthesize SACs.